THE USE OF SHORT FILM NADIA TO IMPROVE STUDENTS’ MASTERY IN IDIOM THROUGH DISCUSSION METHOD AT SMA NEGERI 1 RAYA KAHEAN ACADEMIC YEAR 2021/2022 - Sela Rasmita; Asnawi Asnawi; Nurhafni Siregar (Jurnal Inovasi Penelitian, 2023)
The purpose of this study is to determine whether the use of short films can increase students' ability to increase idioms through the discussion method at SMA Negeri 1 Raya Kahean Academic Year 2021/2022. This study uses an experimental method which is conducted in three procedures. Each procedure consists of, pre-test, treatment and post-test. The sample was divided into two groups, 30 students as an experimental group taken from class XI IPA 1 and 30 students as a control group taken from class XI IPA 2. In collecting data, the test used by researchers were pre-test and post-test. Observations and multiple-choice test instruments were used in this study. The results showed that using Nadia's Short Film through the discussion or group method had a positive effect on increasing idiom knowledge in students of SMA Negeri 1 Raya Kahean Academic Year 2021/202 This can be proven based on the research results in the experimental group, previously the highest student pre-test result was 65 and the lowest was 45, and the highest student post-test result was 85 and the lowest was 70. As for the research results in the control group, the highest student pre-test result was 55 and the lowest was 40, and the highest student post-test result was 70 and the lowest was 50. It shows that students are helped in increasing knowledge with Short Film media followed by the discussion method. Further research is also needed in elaborating and finding more techniques to solve this problem in learning